Oxidative stress Induced by polystyrene microplastics in HEK 293 cells: exploring the impact on the NRF2 pathway - Slabber, Johann (Stellenbosch : Stellenbosch University, 2026)
Thesis (MSc)--Stellenbosch University, 2025.